Impact of physical activity and BMI on health-related quality of life in overweight Indian adolescents: A randomized controlled study - Prateek Srivastav; K. Vaishali; H. Vinod Bhat; Suzanne Broadbent (Obesity Pillars)
Background: Health-related quality of life (HRQOL) is a critical yet often overlooked component of adolescent obesity management. While physical activity (PA) and body mass index (BMI) are established markers of health, their combined influence on HRQOL in Indian adolescents remains underexplored. Objective: To examine how PA and BMI influence overall and domain-specific HRQOL in overweight and adolescents with obesity following a structured lifestyle program. Methods: In this randomized controlled study, 604 adolescents (aged 11–16 years) with BMI above the 85th percentile were recruited from schools in Udupi, India. Individuals were randomized into three groups: multifactorial strategy (MFI: exercise, lifestyle education, behavioral counseling), exercise-only (EX), and Control group (CON). PA was measured using the Physical Activity Questionnaire for Adolescents (PAQ-A), and HRQOL was measured via the Pediatric Quality of Life Inventory (PedsQL 4.0). Linear mixed-effects models evaluated associations between PA, BMI, and HRQOL over a 12-month period, which included a 12-week intervention followed by 9 months of follow-up. Results: PA was linked with better HRQOL in the MFI (β = 9.30, p < 0.001) and EX (β = 4.47, p < 0.001) groups. Interestingly, higher BMI correlated with better HRQOL scores in both program arms. The CON group showed no meaningful association between PA and HRQOL. The domain-level analysis found that PA and BMI were positively linked to physical, emotional, social, and school functioning in both program groups, with more pronounced effects in the MFI group. The CON group showed improvement only in emotional functioning related to BMI. Conclusion: Structured PA programs, especially those combining education and behavioral support, notably enhance the quality of life among overweight Indian adolescents. These findings reinforce the importance of focusing not solely on weight loss, but on holistic, behavior-driven health outcomes in adolescent obesity care. Clinical trial registration: CTRI/2019/04/018,834.